Experimental Study on the Uplift Bearing Capacity of Pre-Drilled Planted Piles in Isolated Stone Strata Based on Transparent Soil Technology - Wenli Liao; Qipeng Cai; Xiangyu Guo; Hao Lin; Jiajin Zhou; Shizhuo Su (Applied Sciences)
The presence of isolated stones in the soil layers of engineering sites has significantly increased. Currently, the existing methods for dealing with isolated stones are inadequate to meet engineering needs. This paper combines pile-planting technology with isolated stones to incorporate them into the load-bearing system, resulting in a new type of pre-drilled composite pile suitable for isolated stone sites. A visualization testing system for pile-soil deformation is developed using Particle Image Velocimetry (PIV) technology and transparent soil, conducting non-intrusive model tests on pile-planting and boulder-capped piles under different uplift load conditions, and comparing the results with a discrete-continuous coupled three-dimensional numerical model analysis. The results indicate that when an isolated stone with a cross-sectional area four times that of the pile exists at the pile tip, the ultimate pullout bearing capacity of the pile increases by a factor of two. Regarding the distribution of internal and external side friction resistances of the core and outer concrete of the piles, the internal friction resistance of piles without isolated stones is approximately 1.47 times that of the external friction resistance and about 0.8 times the ratio of the diameters of the pile and core. For piles with isolated stones at the tip, the internal friction resistance is approximately 1.37 times that of the external friction resistance. Under the ultimate load, the displacement field around the pile without an isolated stone exhibits an “inverted triangular” distribution; the displacement field around the pile with an isolated stone at the tip exhibits a “trapezoidal” distribution. This study investigates the bearing capacity and load transfer mechanisms of the new pre-drilled composite piles in isolated stone engineering sites, and the research findings may provide new solutions for similar construction projects involving rubble reclamation.